A meta-analytic test of organizational culture's association with elements of an organization's system and its relative predictive validity on organizational outcomes - Hartnell, Chad A; Ou, Amy Y; Kinicki, Angelo J; Choi, Dongwon; Karam, Elizabeth P (Journal of applied psychology, 2019)
Organizational culture is an important predictor of organizational effectiveness, but it is also part of an organizational system that consists of highly interdependent elements such as strategy, structure, leadership, and high performance work practices (HPWPs). As such, accounting for the effect of culture's system correlates is important to specify more precisely organizational culture's predictive value for organizational outcomes. To date, however, efforts to connect culture with its system correlates have proceeded independently without integration. This trend is problematic because it raises questions about the strength of culture's association with its system correlates, and it casts uncertainty about organizational culture's predictive validity for organizational outcomes relative to other elements of an organization's system. We addressed these issues by conducting a meta-analysis based on 148 independent samples (N = 26,196 organizations and 556,945 informants). Results generally supported hypothesized predictions linking culture with strategy, structure, leadership, and HPWPs. Meta-analytic regressions and relative weight analyses further revealed that culture dimensions explained unique variance in effectiveness criteria after controlling for the effects of leadership and HPWPs but varied across effectiveness criteria in terms of relative importance. We discuss theoretical and practical implications and highlight several avenues for future research. (PsycINFO Database Record (c) 2019 APA, all rights reserved).